Transformasi Paradigma Bimbingan dan Konseling Islam di Era Society 5.0: Kecerdasan spiritual dan digital - Laora Benro (Conseils : Jurnal Bimbingan dan Konseling Islam, 2026)
Technological developments in the era of Society 5.0 have encouraged all sectors of education and human services to transform, including Islamic guidance and counseling. The traditional counseling paradigm, which focuses on face-to-face relationships, is now shifting towards an integrative model that combines spiritual intelligence and digital intelligence. This article aims to analyze the paradigm shift in Islamic Guidance and Counseling (BKI) in the context of digital transformation, as well as how spiritual intelligence continues to function as the core value and ethical foundation in the service process. The writing method uses a literature study of books, SINTA journal articles, and publications related to educational technology. The results of the analysis show that BKI has undergone shifts in terms of epistemology, service strategies, counselor competencies, and counseling media, but it still maintains its main objectives, namely tazkiyah an-nafs and character building. This article offers an integrative Spiritual–Digital Counseling Framework model as a new direction for the development of BKI in the era of a super-smart society.